Oral exposure of pigs to the mycotoxin deoxynivalenol does not modulate the hepatic albumin synthesis during a LPS-induced acute-phase reaction. Issue 8 (November 2020) - Dänicke, Sven; Bannert, Erik; Tesch, Tanja; Kersten, Susanne; Frahm, Jana; Bühler, Susanne; Sauerwein, Helga; Görs, Solvig; Kahlert, Stefan; Rothkötter, Hermann-Josef; Metges, Cornelia C; Kluess, Jeannette
The sensitivity of pigs to deoxynivalenol (DON) might be influenced by systemic inflammation (SI) which impacts liver. Besides following acute-phase proteins, our aim was to investigate both the hepatic fractional albumin (ALB) synthesis rate (FSR) and the ALB concentration as indicators of ALB metabolism in presence and absence of SI induced by LPS via pre- or post-hepatic venous route. Each infusion group was pre-conditioned either with a control diet (CON, 0.12 mg DON/kg diet) or with a DON-contaminated diet (DON, 4.59 mg DON/kg diet) for 4 wk. A depression of ALB FSR was observed 195 min after LPS challenge, independent of feeding group or LPS application route, which was not paralleled by a down-regulated ALB mRNA expression but by a reduced availability of free cysteine. The drop in ALB FSR only partly explained the plasma ALB concentrations which were more depressed in the DON-pre-exposed groups, suggesting that ALB levels are influenced by further mechanisms. The abundances of haptoglobin, C-reactive protein, serum amyloid A, pig major acute-phase protein, fibrinogen and LPS-binding protein mRNA were up-regulated upon LPS stimulation but not accompanied by increases in the plasma concentrations of these proteins, pointing at an imbalance between synthesis and consumption.